Light from Ancient Campfires: Archaeological Evidence for Native Lifeways on the Northern Plains - Trevor R. Peck (Athabasca University Press, 2011)
Light from Ancient Campfires is the first book in twenty years to gather together a comprehensive prehistoric archaeological record of the Northern Plains First Nations. In this important examination of the region's earliest inhabitants, author Trevor R. Peck reviews the many changes of interpretation that have occurred in relevant literature published during the last two decades. Beginning with the earliest archaeological evidence for people in Alberta, Light from Ancient Campfires covers each period in chronological sequence. Throughout his research, Peck asks the following questions: What defines the cultural entity? How has our notion of it changed with increased information? What is the current state of thought concerning this issue? Light from Ancient Campfires provides a new definition for each archaeological phase, setting previous literature in a new light.